Entacapone and Prostate Cancer Risk in Patients With Parkinson's Disease. Issue 5 (16th January 2015) - Korhonen, Pasi; Kuoppamäki, Mikko; Prami, Tuire; Hoti, Fabian; Christopher, Solomon; Ellmén, Juha; Aho, Valtteri; Vahteristo, Mikko; Pukkala, Eero; Haukka, Jari
ABSTRACT Background The association between Parkinson's disease (PD) and prostate cancer, both common in elderly men, is disputable. In the STRIDE‐PD study, prostate cancer developed in 9 patients (3.7%) receiving levodopa/carbidopa with entacapone, a catechol‐O‐methyltransferase inhibitor, versus 2 cases (0.9%) without entacapone. The current pharmacoepidemiological study aimed to determine whether entacapone increases prostate cancer incidence or mortality in PD patients and whether cumulative exposure affects these rates. Methods We performed a retrospective cohort study using population‐wide health care registers with patient‐level linkage. Prostate cancer incidence and mortality were modeled by Cox's proportional hazards models. Results and Conclusions Use of entacapone with l‐dopa/dopa decarboxylase inhibitor caused no increased risk of prostate cancer incidence (hazard ratio [HR]: 1.05; 95% confidence interval: 0.76‐1.44) or mortality (0.93; 0.43‐1.98). The HR for cumulative entacapone use of >360 days versus never‐use was 0.82 (0.56‐1.18) for prostate cancer incidence and 1.27 (0.60‐2.72) for prostate cancer mortality. © 2015 International Parkinson and Movement Disorder Society © 2015 International Parkinson and Movement Disorder Society